2020
DOI: 10.1002/aocs.12339
|View full text |Cite
|
Sign up to set email alerts
|

GxE Effects on Tocopherol Composition of Oils from Very Old and Genetically Diverse Olive Trees

Abstract: Tocopherols are compounds with high biological activity, beneficial for human health that can be found in vegetable oils like olive oil, contributing for its resistance to oxidation. In this work, the tocopherol contents of olive oils extracted from centenarian olive trees of six cultivars (cvs. Lentisca, Madural, Rebolã, Redondal, Verdeal, and Verdeal Transmontana) were evaluated during five consecutive crop seasons (2013)(2014)(2015)(2016)(2017). Three tocopherol isoforms (α-, βand γ-tocopherols) were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The total content of tocopherols (135-579 mg kg −1 ), as well as those of different isoforms, was in agreement with the literature values [64,70,83]. The genotype effect on tocopherols was reported also in previous studies [26,64], even if α_TOC was also reported to be under environmental control [45,70].…”
Section: Discussionsupporting
confidence: 90%
“…The total content of tocopherols (135-579 mg kg −1 ), as well as those of different isoforms, was in agreement with the literature values [64,70,83]. The genotype effect on tocopherols was reported also in previous studies [26,64], even if α_TOC was also reported to be under environmental control [45,70].…”
Section: Discussionsupporting
confidence: 90%
“…Redondilla and Royuella had the lowest amount (175.9 mg/kg). It is known that a higher content of vitamin E corresponds to greater resistance to oxidation [28]. Nevertheless, other factors must…”
Section: Tocopherols Compositionmentioning
confidence: 99%
“…When it is intended to value centenarian olive tree specimens, the search for differentiated olive oils with specific and desired chemical and sensory attributes is usually taken into account. For example, the search for specimens with high amounts of antioxidants, such as phenolic compounds and tocopherols [20,21], as well as exceptional sensory properties, have been explored [2]. Recently, some studies reported that genetic effects are the main source of variation for most olive oil constituents, leading to great variability in the composition of olive oils [22][23][24].…”
Section: Introductionmentioning
confidence: 99%